The difference in perception on the importance of sex education for adolescence between elderly and adolescence - Soewadi Soewadi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background: Sexual life is important in the life of a person, i:e. the interaction between male and female. An adequate knowledge of sex helps one to avoid a variety of problems in living, helps prevent sexual dysfunctions among other disorders, adds enjoyment of sex itself, and probably enhances life in numerous other ways. However, modern societies restrict and control the sexual behavior and expression of the young, so that the sex instinct does not prepare young person for a successful sex life.Objective: To identify the difference in perception of the importance of sex education among adolescence between elderly and adolescence.Subjects: The study was carried out in Yogyakarta among elderly (retired person) and adolescence (students in the first year of their undergraduate study).Methods: The study was undertaken using structured questionnaires distributed to subjects selected using simple random sampling.Study design: cross-sectional survey. Statistical analysis: Chi-square technique.Results: The results showed that there was a significant difference between the group of elderly subjects and adolescence according to the perception of the importance of the sex education among adolescence (p<0.05).Conclusions: there is a relationship between age and the perception on the importance of sex education for adolescence.Key words: sexual education - elderly - adolescence